Violin Teaching in Sanggar Merah Putih: Case Study of Budi Yuntono's Teaching Style - Hery Budiawan; Nurul Ulfa Aulia (Universitas Negeri Medan, 2022)
The purpose of this study is to find out how the teaching style used by Sanggar Merah Putih. The uniqueness of this sanggar is that it uses traditional teaching on musical instruments originating from the western, namely the violin. The research method used is a qualitative research method with a case study approach. The data search method for this study, researchers made observations, literature studies, documentation, and also interviews to several speakers including sanggar teachers and students at Sanggar Merah Putih which were carried out offline and also online. The results obtained in this study, Sanggar Merah Putih applied several methods, namely oral methods, demonstrations, and imitations in its teaching. sanggar also applies the technique of memorizing the notation of songs instead of reading the notation. Teachers use number notation and also solmization in their teaching, instead of using block note scores as in the teaching of violin instruments in general. With teaching techniques and methods like this, it is able to make children faster to master their musical instruments. Sanggar Merah Putih plays many songs from various genres, ranging from traditional songs, Country, Irish, Pop, and others.